The zoophycos ichnofacies in the Río Mayer Formation (Austral Basin, Patagonia): palaeoenvironmental controls - Richiano, Sebastián Miguel (2013)
The Río Mayer Formation (Berriasian-Albian) is part of the initial infill of the Austral Basin, southwestern Gondwana. At Los Glaciares National Park (Santa Cruz Province), specifically at the Seccional Río Guanaco, seven detail sedimentary sections were performed. From a sedimentological point of view this unit is mainly composed of black shales interbedded with marls and fine-grained sandstones. The combinations of these lithologies allow the division of the unit in three major sections. The lower section (Berriasian- lower Valanginian) is almost exclusively composed of black shales and is characterized by the absence of traces fossils. The middle section is a 40 m succession of marls with thin intercalations of sandy levels. In this section there is a well preserved Zoophycos ichnofacies which was developed in a moment of minimal sediment input from the continent during the Valanginian- lower Hauterivian. Finally, the upper section of the Río Mayer Formation (Hauterivian-Albian) consist of an interbedded of black massive shales and thin fine-grained sandstones. Only in the last few meters of this section trace fossils were recorded and again is present a Zoophycos ichnofacies, but in this case associated with an Ophiomorpha rudis ichnosubfacies. The sandy levels are related to the distal deltaic influence from the Piedra Clavada Formation during the Aptian-Albian. Overall, the Río Mayer Formation presents two different expressions of the Zoophycos ichnofacies (consisting of Zoophycos and Chondrites ichnogenus). First, in the middle section of the unit, this ichnofacies is very well developed, highly evolved, with bioturbation index (BI) between 3 or 4, for the Zoophycos ichnogenus the tunnels are nearly of 1 cm in diameter and more than 1 m in length. The environmental context that governs this sedimentation is a Transgresive System Tract associated with very low sedimentation rates. On the other hand, the ichnofacies in the upper section of the unit is less evolved, with BI between 0 to 1, tunnels of Zoophycos shows short developed and 0.3 cm in diameter, and is associated with an Ophiomorpha rudis ichnosubfacies. The main context include a deltaic progradation over the distal platform, this situation generated the higher sedimentation rates of the studied unit. In conclusion, the highly different evolution and development of the Zoophycos ichnofacies in the Río Mayer Formation was controlled by the palaeoenvironmental stability reflected in the sedimentation rates. When the palaeoenvironments were stabled and with low sedimentation rates, the sedimentary rocks are highly bioturbated by the Zoophycos ichnofacies. On the contrary, in less stables palaeoenvironment, related to distal turbiditic flows and higher sedimentation rates the ichnofacies shows less evolve developments.